Enhancing tribological performance of electric vehicle lubricants: Nanoparticle-enriched palm oil biolubricants for wear resistance - Nugroho, Agus; Muhammad, Kozin; Rizalman, Mamat; Bo, Zhang; Mohd Fairusham, Ghazali; Muhammad Prisla, Kamil; Prabowo, Puranto; Diah Ayu Fitriani, .; Siti Amalina Azahra, .; Kusuma Putri, Suwondo; Putri Sayyida Ashfiya, .; Wan Muhammad Noor Sarbani, Mat Daud (Elsevier Ltd, 2024)
The transition to electric vehicles (EVs) calls for sustainable advancements in automotive lubricants, as traditional fossil-fuel-based products pose environmental challenges. Palm oil-based biolubricants enriched with nanoparticles present a promising eco-friendly alternative that meets the thermal and tribological demands of EVs. This paper aims to analyze the development of nanoparticle-enriched palm oil-based biolubricants, aimed at improving the sustainability and performance of electric vehicle (EV) lubrication systems. The critical findings highlight that integrating nanoparticles such as graphene, titanium dioxide, and aluminum oxide into palm oil-based lubricants significantly enhances their tribological properties. These enhancements include a 26.21%–34% reduction in coefficient of friction (COF), a 12.99%–30% reduction in wear, and improved thermal stability. The study found that nanoparticle-enriched biolubricants outperformed traditional options in terms of friction and wear under high-temperature and pressure conditions, as supported by regression analysis. The study demonstrates that nanoparticle-enriched biolubricants offer a viable eco-friendly alternative to conventional lubricants, lowering the environmental impact by reducing greenhouse gas emissions and energy consumption. This innovation has significant implications for both the environment and industry, offering a sustainable solution that reduces dependency on fossil fuels, enhances EV efficiency, and aligns with global sustainability goals. Besides, this paper discusses biolubricants drawbacks and future studies direction.